THE EFFECT OF THREE STAGE FISHBOWL DECISION STRATEGY IN COMPREHENDING NARRATIVE TEXTS BY THE SECOND YEAR STUDENTS OF SMAN 2 KUANTAN HILIR - Andriana, Sonika Andriana Sonika; Syarfi, M.Syarfi; ', Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this experimental research was to know the effectiveness of the Three Stage Fishbowl Decision Strategy in comprehending such a reading text as narrative texts. The subject of this research were 46 second year students of SMAN 2 Kuantan Hilir, it consisted of two classes; Experimental class and control class. In this research, the data were collected through two ways: Pre-test and Post-test. The findings showed that the application of three stage fishbowl decision strategy can affect the students in comprehending narrative texts. At the pre-test, the average score of students in experimental class and control class was 58.61 and 58.78. At the post-test, the average score of experimental class and control class was 75.13 and 61.39.It showed us that the post-test of experimental class was higher than control class. Based on the result of the research, English teacher are suggested to use three stage fishbowl decision strategy to affect the students in comprehending narrative texts.Keywords: Three Stage Fishbowl Decision Strategy, Comprehending, Narrative texts